Annotating the Field: Investigating the Affordances of Mixed Reality for Learning Beyond the Classroom - Kenneth Y. T. Lim; Aaron J. C. Liang; Yuyue Fang; Bryan Z. W. Kuok (Virtual Worlds, 2025)
While educational excursions are widely acknowledged to enhance student learning through immersive, real-world experiences, there is limited research on how students can best capture and retain knowledge during such activities. Traditional note-taking methods, such as pen and paper or digital devices, may be inadequate for recording spatial or multimodal information encountered in these dynamic environments. With the emergence of mixed reality (MR) technologies, there is an opportunity to explore spatial, immersive note-taking that aligns with the dynamic nature of field-based learning. This study compares the effectiveness of mixed reality, pen and paper, and digital note-taking during educational excursions. A total of 50 participants in grades 7 through 12 used the Apple Vision Pro headset for mixed reality notes, mobile phones for digital notes, and clipboards paired with a pen and paper for traditional notes. The information encountered was categorised as physical, textual, or video-based. The effectiveness was evaluated through three measures: content extracted and organised in notes, post-activity quizzes on retention and critical thinking, and participant feedback. For physical information, mixed reality significantly improved the content extraction and retention. For textual information, mixed reality yielded more content, but pen and paper outperformed it in terms of organisation. Statistically, all the note-taking methods were equally effective in the remaining aspects. Although mixed reality shows potential to be integrated into educational excursions, participant feedback highlighted discomfort with the headset, suggesting that mixed reality should complement, not replace, traditional approaches.